STUDENTS' PERCEPTION IN USING DEBATE TECHNIQUE TO DEVELOP STUDENTS' SPEAKING SKILLS - Putri Meldia; Melyann Melani (Universitas Mahaputra Muhammad Yamin, 2022)
This study aimed to understand how students thought about using classroom debate to improve students speaking skill. This study used descriptive quantitative approach by distributing a questionnaire with thirty statements and a 5-point Likert scale to collect some of the data. The informations were collected using a detailed questionnaire that was distributed to thirty respondents. Some problems were found in conducting debate; first, debate burdened the students, second, they felt loaded when a debate is running because they must respond to the motion given for three minutes without sufficient preparation, third, the lack of ideas and vocabulary related to the motion had also been identified as what made it difficult.. The result of the research reveals that a larger percentage of the students had a positive perception of the three aspects of the debate technique namely the benefits of debate, the part of debate, and the procedure of debate. In addition, most students selected the affirmative response.